Evolution of IMF By induced asymmetries during substorms: Superposed epoch analysis at geosynchronous orbit - Ohma, Anders; Laundal , Karl Magnus; Reistad , Jone Peter; Østgaard , Nikolai (Frontiers in Astronomy and Space Sciences, 2022)
The By component of the magnetic field inside the magnetosphere is positively correlated with the By component of the Interplanetary Magnetic Field (IMF). This leads to asymmetries in aurora, plasma convection and electric currents between the northern and southern hemispheres It has been demonstrated that magnetic conjugate locations in the northern and southern ionosphere become less displaced during magnetospheric substorms, which are associated with enhanced reconnection in the near-Earth tail. Here we directly address how the average By component in the magnetotail evolves relative to substorm onset by performing a superposed epoch analysis of the magnetic field observed at nightside geosynchronous orbit during periods with dominant IMF By. The observations demonstrate that the average |By| in the magnetotail increases during the loading phase prior to onset. |By| maximizes in the expansion phase and is subsequently reduced during the remaining unloading phase. The observed trends become more pronounced using substorm onset lists that on average identify stronger substorms. Since dayside reconnection dominates over tail reconnection during the loading phase, whereas tail reconnection dominates during the unloading phase, the results demonstrate how asymmetries build up during periods with low tail reconnection and are reduced during periods with enhanced tail reconnection in agreement with previous case studies of conjugate auroral substorm features.